Adaptation to compound climate risks: A systematic global stocktake - Simpson, Nicholas P; Williams, Portia Adade; Mach, Katharine J.; Berrang-Ford, Lea; Biesbroek, Robbert; Haasnoot, Marjolijn; Segnon, Alcade C; Campbell, Donovan; Musah-Surugu, Justice Issah; Tom Joe, Elphin; Nunbogu, Abraham Marshall; Sabour, Salma; et al. (Elsevier, 2023)
This article provides a stocktake of the adaptation literature between 2013 and 2019 to better understand how adaptation responses affect risk under the particularly challenging conditions of compound climate events. Across 39 countries, 45 response types to compound hazards display anticipatory (9%), reactive (33%), and maladaptive (41%) characteristics, as well as hard (18%) and soft (68%) limits to adaptation. Low income, food insecurity, and access to institutional resources and finance are the most prominent of 23 vulnerabilities observed to negatively affect responses. Risk for food security, health, livelihoods, and economic outputs are commonly associated risks driving responses. Narrow geographical and sectoral foci of the literature highlight important conceptual, sectoral, and geographic areas for future research to better understand the way responses shape risk. When responses are integrated within climate risk assessment and management, there is greater potential to advance the urgency of response and safeguards for the most vulnerable.